A novel fucolectin from Apostichopus japonicus with broad PAMP recognition pattern. Issue 77 (June 2018) - Wang, Ying; Xue, Zhuang; Yi, Qilin; Wang, Hui; Wang, Lingling; Lu, Guangxia; Liu, Yu; Qu, Chen; Li, Yannan; Song, Linsheng
Abstract: F-type lectin (also known as fucolectin) is a newly identified family of fucose binding lectins with the sequence characters of a fucose binding motif and a unique lectin fold (the "F-type" fold). In the present study, a fucolectin was identified from sea cucumber Apostichopus japonicus (designated Aj FL-1). The open reading frame (ORF) of Aj FL-1 was of 546 bp, encoding a polypeptide of 181 amino acids with a predicted molecular mass of about 20 kDa. The deduced amino acid sequence of Aj FL-1 shared 30%-40% similarity with the fucolectins from other animals. There were a typical F-type lectin domain (FLD) (residues 39-180) and a signal peptide (residues 1-24) in Aj FL-1. The mRNA transcript of Aj FL-1 could be detected by qRT-PCR in various tissues, such as intestinum, coelomocytes, respiratory tree, tentacle, and body wall, while undetectable in the gonads and longitudinal muscle. The mRNA expression level of Aj FL-1 in coelomocytes was significantly up-regulated (47.06-fold to that in control group, p  < 0.05) at 12 h after Vibrio splendidus challenge. Immunofluorescence assay showed that Aj FL-1 protein was mainly distributed on the membrane, while few in cytoplasm of coelomocytes in sea cucumber. The recombinant Aj FL-1 (r Aj FL-1) could bind lipopolysaccharide (LPS), peptidoglycan (PGN), mannan (MAN) and fucose (FUC), and exhibited a broader binding activities towards Gram-negative bacterium Escherichia coli, Gram-positive bacterium Micrococcus luteus, as well fungus Pichia pastoris . In addition, r Aj FL-1 could strongly promote the agglutination of fungus P. pastoris . These results indicated that Aj FL-1 was a novel member of fucose-binding lectin family, which functioned as a pattern recognition receptor with broad spectrum of microbial recognition, and involved in innate immune response of sea cucumber. Highlights: A novel Fucolectin was identified from Apostichopus japonicus. Aj FL-1 mRNA was expressed universally in various tissues. r Aj FL-1 exhibited binding activity to various PAMPs and bacteria. r Aj FL-1 showed a significant agglutination effect toward P. pastoris . The protein of Aj FL-1 mainly localized on the membranes of coelomocytes.